Recent Advances of Processing and Detection Techniques on Crustacean Allergens: A Review - Xin Qu; Zekun Ma; Xuli Wu; Liangtao Lv (Foods)
Crustaceans are delicious and highly nutritional food. However, crustaceans are one of the main food allergens, causing severe public health issues. Thus, it is important to increase the knowledge on crustacean allergens and protect the health of sensitized individuals. This review systematically summarizes the basic information on major crustacean allergens’ characteristics, structures, and function. It also summarizes the latest evaluation and detection methods of crustacean allergens. In addition, various processing techniques to alleviate crustacean’s allergenicity are discussed and compared. A host of multiplex approaches as innovative research is attractive to decrease crustacean allergenicity. In addition, the strategies to address the risk of crustacean allergens are also reviewed and discussed in detail. This review provides updates and new findings on crustacean allergens, which helps better understand crustacean allergy and provide novel strategies for its prevention and management.